Development of Information and Communication Technologies (ICT) to disseminate nuclear physics in Brazil. Issue 1 (1st September 2022) - Foltran, M H; Teixeira, E A; Carlson, B V
Abstract: The wide range of practical applications regarding Nuclear Physics makes it a field with extreme relevance for research, industry, and scientific advances worldwide. However, despite its importance, there is no considerable dissemination of this topic in Brazil. In this project, we developed different Information and Communication Technologies (ICT) to disseminate nuclear physics-related opportunities, events, scholarships, and other types of relevant content that may be of interest to the academic and non-academic public. Under the name Física Nuclear Brasil, a website portal was developed and social media profiles were created to value, strengthen and recognize the importance of such a relevant scientific field in Brazil. In addition, several contents were created to share institutions and opportunities, such as scholarships and jobs related to nuclear physics, as well as articles (scientific and non-scientific ones) related to the field. As a result, the portal is intended to act as a community source with updated and reliable nuclear physics and physics content. We expect that all content published under this project would help in the dissemination of nuclear physics in Brazil as a path to remedy the lack of reliable sources for this significant scientific area.